RECASTING THE BEST INTERESTS TEST: Safeguarding Sibling Continuity in Indonesian Custody Adjudication - Hamrany, Ahmad Khairun; Rusydi, Bustanul Arifien (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
The absence of clear evaluative guidelines for child custody determination in Indonesia has led judicial reasoning to be dominated by parent–child relational assessments. In contrast, the continuity of children’s relationships with their siblings is frequently overlooked. Yet sibling bonds can be crucial protective factors for children’s adjustment following parental divorce. The study aims to map how judges operationalize the best interests of the child principle in custody cases involving more than one child; to assess the consideration given to sibling relationships, psychosocial evidence, and children’s participation; and to propose regulatory strengthening. Using a normative–empirical design, this study examines how judges assess children’s psychosocial circumstances as a basis for deciding custody disputes. Data were collected through purposive sampling of court judgments and mediation outcomes in child-custody disputes involving multiple children. Qualitative analysis and reflexive thematic analysis were employed to map the ratio decidendi and to identify operational gaps in custody adjudication concerning sibling relationships, psychosocial evidence, and children’s participation across judicial decisions. The findings show that judges consistently invoke the best interests of the child as the guiding principle, but operationalize it through a narrow focus on the individual parent–child relationship. Decisions to keep siblings together or to separate them are made without a transparent analysis of the psychosocial implications for the children. By reframing sibling-relationship continuity as a prima facie element of the best-interests principle, this study proposes a phased strengthening of Indonesia’s custody adjudication framework through Supreme Court circular guidance and legislative reform.